Kepatuhan Syariah pada Produk Musharakah di Bank Syariah Indonesia - Sujian Suretno (JURNAL INDO-ISLAMIKA, 2019)
This article assesses whether or not the syari`ah bank is in its practice similar to the conventional one. This study uncovers that these two types of bank have some similarities in their practices of financing cooperations either in terms of their procedures, their administrations, and their principles.